Peat Stabilization using Gypsum and Fly Ash - Kolay, P.K; Pui, M.P (Universiti Malaysia Sarawak, (UNIMAS), 2010)
This paper presents the stabilization of local peat soil from Matang, Sarawak using gypsum and fly ash. Pear soil has been identified as one of the major groups of soils found in Malaysia, which has high compressibility and low shear strength. Presence of soft or peaty soil is a major problem encountered by civil engineers in Sarawak.